Multimodal practical argumentation and behavioral change: an analysis of the “Remember, the Metro is for everyone” campaign - Gonçalves-Segundo, Paulo Roberto; Isola-Lanzoni, Gabriel (Revista da ABRALIN, 2021)
The aim of this paper is to discuss how the verbal and the pictorial modalities interact to construe argumentative meanings in a transport campaign promoted by Lisbon’s subway company in 2018. As an instance of multimodal practical argumentation aimed at behavioral change, the campaign constitutes a significant corpus for discussing a series of relevant issues in the field, such as the illative reconstruction of arguments, the affordances of each modality in schematization, and the operationalization of pictorial analysis in regard to its argumentative potential. By drawing on a dialogue between Social Semiotics and Argumentation Theory, we arrived at the following conclusions: (i) the campaign established verbal and pictorial subcanvases specialized in construing certain parts of the main practical argumentation schemes; (ii) images were inherently tied to the construction of Circumstantial premises, thus exerting a direct role in argumentation, and tended to portray complex representational meanings, with three combined process types; (iii) the most productive argumentation schemes utilized were the instrumental practical reasoning scheme, the argument from values and the argument from consequences; (iv) there were two targeted audiences – the readers/clients in general, usually identified with the affected depicted people, and the clients whose behavior was being targeted in the campaign, represented as transgressors in the pictorial subcanvas